Pompa and Praise in Claudianʼs Panegyrics on the Third, Fourth and Sixth Consulship of Honorius - Baumann, Sally (Sapiens ubique civis, 2023)
The paper deals with three representations of pompae (processions) within Claudian ʼs Panegyrics on the Third, Fourth and Sixth Consulate of Honorius. The depictions of two adventus (Claud. 3 cons. Hon. 125sqq.; Claud. 6 cons. Hon. 543sqq.) and one processus consularis (Claud. 4 cons. Hon. 565sqq.) are examined with regard to content, form, and function and subsequently compared. The comparison shows that all three pompa-passages share common features. These similarities form a design concept through which the passages are connected. At the same time, in terms of length, formal features as well as aspects of content a development can be observed in the adventus-passage in 6 cons. Hon. Honorius, here, outgrows the former versions of himself, represented in Claud. 3 cons. Hon. and Claud. 4 cons. Hon. Similarly, the poet Claudian surpasses himself on a poetic level.